Inhibition of CISD2 promotes ferroptosis through ferritinophagy-mediated ferritin turnover and regulation of p62–Keap1–NRF2 pathway - Yanchun Li; Bing Xu; Xueying Ren; Luyang Wang; Yaqing Xu; Yefeng Zhao; Chen Yang; Chen Yuan; Huanjuan Li; Xiangmin Tong; Ying Wang; Jing Du (Cellular & Molecular Biology Letters, 2022)
Abstract Background CDGSH iron sulfur domain 2 (CISD2) is an iron–sulfur protein with a [2Fe–2S] cluster, which is critical for cell proliferation and iron homeostasis. It has been demonstrated that aberrant expression of CISD2 is associated with the progression of multiple cancers. However, the underlying mechanism of CISD2 in regulating tumorigenesis remains obscure. Methods Bioinformatics strategies were used to investigate the protein interaction network and functional annotation of CISD2. In the functional experiment, cell viability was measured by CCK-8 kit. The levels of cellular reactive oxygen species (ROS), intracellular free iron, lipid peroxides, and lysosomal activity were determined by DCF-DA, RPA, C11-BODIPY, and cathepsin B staining, respectively. The glutathione (GSH) content was determined using a GSH assay kit. Results We showed that knockdown of CISD2 significantly accelerated the Erastin-induced ferroptotic cell death with excess lipid peroxidation, GSH exhaustion, and iron accumulation, while overexpression of CISD2 hindered the sensitivity to Erastin. Further assays via confocal microscopy and western blot exhibited that CISD2 knockdown markedly enhanced the lysosomal activity, and activated ferritinophagy under the exposure of Erastin. Pharmacological inhibition of lysosomal function could inhibit the degradation of ferritin heavy chain (FTH), and attenuate the phenotypes of ferroptosis, such as accelerated iron accumulation and lipid peroxidation. Notably, we found that Erastin-induced compensatory elevation of nuclear factor erythroid 2-related factor 2 (NRF2) could be eliminated in CISD2 depletion cells. Mechanically, CISD2 knockdown promoted the degradation of autophagy adaptor p62 and resulted in an increased binding affinity of Keap1 with NRF2, thus leading to the increased ubiquitination and subsequent degradation of NRF2. Enforced expression of NRF2 reversed the sensitivity of shCISD2 cells to ferroptosis both in vitro and in vivo. Conversely, enforced expression of Keap1 exacerbated the degradation of NRF2, reduced the transcriptional expression of FTH and heme oxygenase 1 (HO-1), increased the oxidative damage, and thus further facilitated ferroptosis. Conclusion Taken together, our current results illustrated two parallel mechanisms involved in the shCISD2-mediated ferroptosis. One was that shCISD2 enhanced the accumulation of free iron via ferritinophagy-dependent ferritin turnover; the other was that CISD2 depletion induced the inhibition of the p62–Keap1–NRF2 pathway, which resulted in oxidative stress and ferroptosis.